Circuitos mercantis do Porto de Santos às Minas de Goiás entre meados do século XVIII e início do XIX (1765-1808) - Sanches, Thiago [UNESP] (2013)
This research investigates the commercial activity in the captaincy of Goiás in the period of 1765-1808. The main hypothesis is that this activity was intended to ensure the sovereignty and the occupation of the Portuguese Empire in the interior of the continent. To demonstrate this hypothesis will be used the correspondences written by royal officials to the Overseas Council, the bureaucratic documentation of the captaincy published in the collection of DIHCSP, the Board of Finance’s papers of São Paulo’s captaincy, the Ombudsman of Santos’ Royal Treasury and the illustrated dissertations from the time that highlighted the importance of internal trade to the valorization of the inland regions of Brazil’s territory